(untitled) (Research, Society and Development, 2021)
Post-menopausal osteoporosis is detrimental to bone metabolism as well as alveolar repair. This osteometabolic disorder is an obstacle to the success of maxillofacial rehabilitations, since a large number of patients are carriers of the disease. Denosumab is widely used as a treatment for post menopausal osteoporosis. This drug exerts an antiabsorptive action by inhibiting RANKL, helping to reduce the bone loss caused by osteoporosis. This study aimed to evaluate the repair bone formed after the extraction of the upper incisor of estrogen-deficient rats treated with anti-RANKL monoclonal antibody. The rats (Rattus novergicus albinus, Wistar) were ovariectomized or SHAM operated (n=36). Half of the ovariectomized rats were treated with osteoprotegerin with an Fc fragment (OPG-Fc; 10mg/kg, twice a week), the other half received saline solution as control. After 30 days the rats had their right upper incisor extracted. After 60 days of extraction, the alveoli were evaluated by immunohistochemical, computerized microtomography and confocal microscopy. The OPG-Fc decreased the percentage of bone volume (BV/TV), thickness (Tb.Th) and number of alveolar trabecules (Tb.N) when compared to groups that received saline solution (p<0.005). The OPG-Fc increased the separation between the trabecules (Tb.Sp) and the porosity (Po.tot) of the reparative alveolar bone (p<0.005). The OPG-Fc decreased immunolabelling for RANKL and TRAP when compared to groups that received saline solution. Treatment with OPG-Fc decreased bone neoformation but preserved preexisting bone tissue. This data is supported by the mineral apposition rate, which showed higher values for OVX/OPG-Fc when compared to the OVX group.